First language acquisition: Grammar in the speech of a two-year old Bangladesh child - Nasrin, Sadia (BRAC University, 2010)
The paper explores the grammar in the speech of a two-year old Bengali-speaking child. Though language acquisition process is still a mystery, linguists throughout the world confirm that it follows a systematic process in case of any language of the world. However, they have tried hard to discover the grammar in the speech of children. This research is such an attempt to apply the theories of first language acquisition to a Bengali speaking child which identifies that children’s speech is ‘grammatical’ as they follow a systematic pattern.